2012
DOI: 10.1074/jbc.m112.405415
|View full text |Cite
|
Sign up to set email alerts
|

LIM Kinase 1 (LIMK1) Interacts with Tropomyosin-related Kinase B (TrkB) and Mediates Brain-derived Neurotrophic Factor (BDNF)-induced Axonal Elongation

Abstract: Background: BDNF promotes axonal outgrowth, whereas the underlying molecular mechanism has remained unclear. Results: LIMK1 interacts with TrkB, and BDNF treatment could induce LIMK1 dimerization and transactivation, which facilitate axonal elongation. Conclusion: LIMK1-regulated actin dynamics is essential for BDNF-induced axonal elongation. Significance: These results revealed a novel mechanism for the BDNF-induced axonal elongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…The growth cone is composed of microtubules and filamentous actin (F-actin), and the actin cytoskeleton is the motivating force for growth cones, and thus F-actin plays a major part in neuronal growth. LIM kinases regulate the structure of the actin cytoskeleton by phosphorylation and inactivation of the actin depolymerization factor cofilin, and activity of LIM kinase is regulated by Rho-GTPase Rac1 [19,20,54]. A growing body of evidence showed that MAPK is related to the cytoskeleton [20], but the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The growth cone is composed of microtubules and filamentous actin (F-actin), and the actin cytoskeleton is the motivating force for growth cones, and thus F-actin plays a major part in neuronal growth. LIM kinases regulate the structure of the actin cytoskeleton by phosphorylation and inactivation of the actin depolymerization factor cofilin, and activity of LIM kinase is regulated by Rho-GTPase Rac1 [19,20,54]. A growing body of evidence showed that MAPK is related to the cytoskeleton [20], but the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…LIM kinases regulate the structure of the actin cytoskeleton by phosphorylation and inactivation of the actin depolymerization factor cofilin, and activity of LIM kinase is regulated by Rho-GTPase Rac1 [19,20,54]. A growing body of evidence showed that MAPK is related to the cytoskeleton [20], but the mechanism is unclear. Based on this, we propose that Mst3b interacts with Rac1 in modulating the F-actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations